Evaluation of Officer Development Program Training - Nisa Ardini; Samuel Lukas (Jurnal Syntax Admiration, 2024)
The previous research indicates that the evaluation of training programs has not addressed the performance aspects of each participant. Therefore, this study aims to evaluate the Officer Development Program (ODP) training using the Kirkpatrick model at the reaction level (training satisfaction), learning (learning outcomes), and behavior. To address this research objective, the research method used in this study is a mixed-method approach. Several instruments, such as questionnaires, tests, and interviews, were employed to gather information. The research subjects were seven ODP participants. The results of the evaluation at the reaction level show that overall, ODP participants are quite satisfied with the onsite training. At the learning level, out of the seven ODP participants, one scored below 60. At the behavior level, all ODP participants did not complete 100% of the required tasks in each department. However, all ODP participants not exhibited behavior in line with the indicators required. From the evaluation results, it can be concluded that the training evaluation for ODP (Officer Development Program) has not been effective in achieving the program's goals. Recommendations for the training program include modifying the learning model to enhance adaptability, resilience, job management, and problem-solving skills.